A case report on two superimposed foreign body coins in esophagus - Gupta, Richa; Mittal, Manish (International Journal of Research in Medical Sciences, 2017)
Foreign body ingestion is a common occurence. We report a case of 8 year old male who presented with history of foreign body ingestion (coin). He had frequent episodes of vomiting along with foreign body sensation. Later on two superimposed foreign body coins were removed by rigid oesophagoscopy.